A convenient room temperature ipso‐nitration of arylboronic acid catalysed by molecular iodine using zirconium oxynitrate as nitrating species: An experimental and theoretical investigation. (6th May 2019) - Mahanta, Abhijit; Gour, Nanda Kishor; Sarma, Plaban Jyoti; Borah, Raju Kumar; Raul, Prasanta Kumar; Deka, Ramesh Chandra; Thakur, Ashim Jyoti; Bora, Utpal
Abstract : A simple and convenient protocol has been developed for ipso ‐nitration of arylboronic acid catalysed by molecular iodine at room temperature, using zirconium oxynitrate as the nitrating species. The protocol is applicable to electronically diverse aryl‐ and heteroarylboronic acid moieties under mild reaction conditions with good to excellent isolated yields. Furthermore, a theoretical investigation has been performed for the same reaction, and reaction profiles are modelled using modern density functional theory (DFT). DFT‐based results support the experimentally observed results. Abstract : Strong acid‐/oxidant‐free conditions Avoids high temperature, ligands, etc. Mild oxidant and nitrating agents are used